Exponential infusion and its pharmacokinetics - Huang Sheng-kai; Meng Xu (Acta Pharmacologica Sinica, 2016)
Here is presented a general kinetic equation for exponential infusion. The exponential infusion for one compartment model is safe and is at will in adjusting the time required to obtain steady state plasma level according to clinical requirements. The plasma concentration can be maintained for a period of time, if necessary, for a long time after the steady state level is attained. The time required to obtain a steady state plasma level by exponential infusion of chloramphenicol is much shorter than that required by constant rate infusion.